Microleakage evaluation of Silorane-based composite and Methacrylate-based composite in class II box preparations using two different layering techniques: An in vitro study - Asha Joseph; Lekha Santhosh; Jayshree Hegde; Srinivas Panchajanya; Reshmi George (Wolters Kluwer Medknow Publications, 2013)
Aim: The aim of this study was to compare the microleakage in Class II box preparations with the gingival margin above and below the cemento-enamel junction (CEJ) restored with Silorane composite and methacrylate composite using two different layering techniques. Materials and Methods: Standardized box preparations (mesial box 1 mm above the CEJ and distal box 1 mm below the CEJ) were prepared in 60 upper premolars. The teeth were randomly divided into four groups containing 15 samples each; Group I: Restored with a Silorane composite using an oblique layering technique, Group II: Restored with Silorane composite using a vertical layering technique, Group III: Restored with methacrylate composite using the oblique layering technique, and Group IV: Restored with methacrylate composite using the vertical layering technique. The samples were stored in distilled water, followed by thermocycling and immersed in 2% methylene blue. The samples were sectioned and evaluated for microleakage at the gingival margin. Statistical Analysis: Kruskal-Wallis, Fischer exact test, Wilicoxon test, and Mann-Whitney U test. Results: Silorane composite had significantly lesser microleakage. No significant difference in microleakage was observed above and below the CEJ for Silorane-based composite. Conclusion: Silorane composite resin showed lesser microleakage compared to methacrylate composite resin. Clinical Significance: The Silorane-based composites improve the marginal adaptation due to their reduced shrinkage, thereby decreasing the residual stress at the adhesive-tooth interface.